STATE-FREELANCE PARTNERSHIP AS AN INSTRUMENT OF INFLUENCE ON INFORMAL EMPLOYMENT - M. I. Glinskaya (Вестник университета)
The author’s tool, whose main task is to attract informally employed people to carry out their activities through the new employment model has been presented. This tool is not a radical solution to combat informal employment, but rather a gentle measure, aimed at increasing the interest of the economically active population to quit shadow employment. In the age of modern technologies, when the problem of computerization of workplaces is relevant, the form of the state-freelance partnership, underlying the proposed tool, will help the population to legalize their income with the least barriers to entry.